Estimating soil erodibility from sonication indexes and other attributes of textural B horizon soils - de Sá, Marcos Aurélio Carolino; de Lima, José Maria; Curi, Nilton; Massaroto, João Aguilar; Marques, João José Granate de Sá e Mello (Pesquisa Agropecuaria Brasileira, 2004)
Soil erodibility is an important factor for estimating soil erosion losses. This factor is an expression of combined soil attributes, which make possible its estimation by equations. The objective of this study was to measure some chemical and mineralogical attributes, and to combine them with aggregate stability indexes from sonication analysis, in equations in order to estimate soil erodibility of textural B horizon soils from Brazil. These attributes were measured for 22 soils that had their erodibility measured from field plots. Attributes of 21 soils were used to adjust the equations. One of the soils (Red-Yellow Argisol) was used to test the equations. From 96 variables, 15 were significantly correlated to soil erodibility. Most of them are represented by the disruption indexes from sonication analysis of A horizon samples. This study resulted in four equations to estimate soil erodibility, whose R2 ranged from 0.83** to 0.91**. The erodibility can be estimated by aggregate stability indices based on sonication analysis.